Ex vivo anti-microbial efficacy of various formaldehyde releasers against antibiotic resistant and antibiotic sensitive microorganisms involved in infectious keratitis - Amponin, Daeryl E. (BMC Ophthalmol, 2020)
BACKGROUND: Corneal infections with antibiotic-resistant microorganisms are an increasingly difficult management challenge and chemically or photochemically cross-linking the cornea for therapy presents a unique approach to managing such infections since both direct microbial pathogens killing and matrix stabilization can occur simultaneously. The present study was undertaken in order to compare the anti-microbial efficacy, in vitro, of 5 candidate cross-linking solutions against 5 different microbial pathogens with relevance to infectious keratitis. METHODS: In vitro bactericidal efficacy studies were carried out using 5 different FARs [diazolidinyl urea (DAU), 1,3-bis(hydroxymethyl)-5,5-dimethylimidazolidine-2,4-dione (DMDM), sodium hydroxymethylglycinate (SMG), 2-(hydroxymethyl)-2-nitro-1,3-propanediol (NT = nitrotriol), 2-nitro-1-propanol (NP)] against 5 different microbial pathogens including two antibiotic-resistant species [methicillin-sensitive Staphylococcus aureus (MSSA), methicillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant Enterococcus (VRE), Pseudomonas aeruginosa (PA), and Candida albicans (CA)]. Standard in vitro antimicrobial testing methods were used. RESULTS: The results for MSSA were similar to those for MRSA. DAU, DMDM, and SMG all showed effectiveness with greater effects generally observed with longer incubation times and higher concentrations. Against MRSA, 40 mM SMG at 120 min showed a > 95% kill rate, p < 0.02. Against VRE, 40 mM DAU for 120 min showed a > 94% kill rate, p < 0.001. All FARs showed bactericidal effect against Pseudomonas aeruginosa, making PA the most susceptible of the strains tested. Candida showed relative resistance to these compounds, requiring high concentrations (100 mM) to achieve kill rates greater than 50%. CONCLUSION: Our results show that each FAR compound has different effects against different cultures. Our antimicrobial armamentarium could potentially be broadened by DAU, DMDM, SMG and other FARs for antibiotic-resistant keratitis. Further testing in live animal models are indicated.